2020
DOI: 10.3233/jad-201029
|View full text |Cite
|
Sign up to set email alerts
|

Burnout of Healthcare Workers in Acute Care Geriatric Facilities During the COVID-19 Crisis: An Online-Based Study

Abstract: Background/Objective: The COVID-19 crisis has been increasing the burden of healthcare workers in acute care geriatric facilities. These workers have been dealing with drastic changes in the care they provide to their residents including cancelation of group activities and communal dining and even restrictions of activities outside rooms. Healthcare workers have also been devoting more time and energy to perform COVID-related medical duties. Geriatric facilities have been facing shortages in equipment and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
0
31
1
2
Order By: Relevance
“…However, some studies have found a reduction in BOS during the COVID-19 outbreak: for example, in US neurosurgeons [56], and in Chinese frontline nurses, compared with ordinary ward workers [57]. A relatively low level of burnout was also observed in healthcare workers in French geriatric facilities providing acute care [58]. There was no association between burnout and exposure to the consequences of COVID-19 among French paediatric residents [59].…”
Section: Discussionmentioning
confidence: 98%
“…However, some studies have found a reduction in BOS during the COVID-19 outbreak: for example, in US neurosurgeons [56], and in Chinese frontline nurses, compared with ordinary ward workers [57]. A relatively low level of burnout was also observed in healthcare workers in French geriatric facilities providing acute care [58]. There was no association between burnout and exposure to the consequences of COVID-19 among French paediatric residents [59].…”
Section: Discussionmentioning
confidence: 98%
“…Burnout, however, is a morbid condition that occurs after exposure to chronic stress and is therefore not the first indicator of mental health that can be altered by an epidemic [ 16 ]. There are conflicting findings on the epidemiology of burnout among HCWs working in COVID-19 wards: some studies have found a reduction in burnout rates, for example in US neurosurgeons [ 17 ], in French geriatric facilities [ 18 ], and in Chinese frontline nurses, compared with ordinary ward workers [ 19 ]. The mental health of HCWs can vary according to many factors and is hardly homogeneous for all groups of workers, even in the same company or department.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the psychological impacts of the COVID-19 pandemic on health professionals, mostly physicians and nurses, is rapidly emerging (7,8). A few studies have directly addressed burnout symptoms (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), including a recent meta-analysis that reported a pooled prevalence of 37.4% among healthcare workers (26).…”
Section: Introductionmentioning
confidence: 99%